Application of The Production Unit Method to Calculate Accumulated Depreciation of Factory Machinery using The Django Model - Pratama, Bagus Aji; Ilka Zufria; M. Fakhriza (Bahasa Indonesia, 2024)
The research was carried out with the aim of making it easier for companies to record and make depreciation reports on factory machines by utilizing existing information systems, to apply the service hours and production unit method in determining depreciation reports on factory machines in companies, to carry out analysis of depreciation data on factory machines in companies, to design and build a system for calculating depreciation of factory machines using the service hour method and the production unit method and to implement a comparison of the service hour method and the production unit method in the factory machine depreciation system. The problem faced by the company is that there is no application program for calculating depreciation on factory machines every month, so it takes quite a long time to determine the amount of depreciation on factory machines and the accumulated depreciation of factory machines every month and the reports obtained are less effective and less efficient. And in determining depreciation of processing factory machines, a special method has not been used to calculate depreciation of factory machines. The company still has many weaknesses, including recording errors, calculation errors, and also the process of making reports which takes a relatively long time.